Method for producing rare earth sintered magnet

By controlling the moisture content of the raw alloy powder in the manufacturing process of the R-T-B system sintered magnet, modifying the grain boundary of the two grains, solving the problems of coercive force reduction and irreversible thermal demagnetization at high temperatures, realizing the manufacturing of high-performance magnets, and reducing the dependence on heavy rare earth elements.

CN119724797APending Publication Date: 2025-03-28PROTERIAL LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411357192.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing R-T-B system sintered magnets have reduced coercive force at high temperatures, and there is an irreversible thermal demagnetization problem. At the same time, the supply of heavy rare earth elements is unstable and the price fluctuates greatly.

Method used

By controlling the moisture content of the rare earth raw material alloy powder in the manufacturing process, the moisture ratio in the oil agent is ensured to be less than 0.005%, so as to prevent moisture from being incorporated into the powder and causing oxidation, thereby modifying the grain boundary of the two grains and improving the performance of the magnet.

Benefits of technology

The control of the fluctuation of the oxygen content of the rare earth-based sintered magnet is achieved, the high-temperature coercive force and irreversible thermal demagnetization performance of the magnet are improved, and the dependence on heavy rare earth elements is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724797A_ABST
    Figure CN119724797A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a rare earth sintered magnet having high Br and high HcJ while reducing the content of heavy rare earth elements, the method comprising: a step for producing a rare earth sintered magnet, a step for recovering the powder particles of the rare earth-based raw material alloy or the aggregate of the powder particles as a recycling raw material; a step for pulverizing the recycled raw material in the oil agent using a pulverizing device; and a step for adjusting the moisture ratio in the oil agent, which is the ratio of the mass of moisture in the oil agent to the mass of the recycled raw material in the oil agent, to 0.005% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a rare earth sintered magnet. Background Art

[0002] RTB sintered magnets (R is a rare earth element, which must contain at least one of Nd and Pr, T is Fe and Co, and more than 90% of T is Fe by mass ratio, and B is boron) as a representative example of rare earth sintered magnets are known to be the highest performance magnets among permanent magnets. They are used in various motors such as electric vehicle (EV, HV, PHV) motors, industrial equipment motors, and home appliances. RTB sintered magnets mainly include R2T 14 The main phase of the B compound and the grain boundary phase located at the grain boundary of the main phase (hereinafter sometimes referred to as "grain boundary"). 14 The B compound is a ferromagnetic phase with a high magnetization.

[0003] RTB sintered magnets have a coercive force H at high temperature. cJ (Hereinafter sometimes referred to as "coercivity" or "H cJ ”) is reduced, resulting in irreversible thermal demagnetization. For this reason, the RTB-based sintered magnets used in electric vehicle motors have high H at high temperatures. cJ demand.

[0004] It is known that in RTB sintered magnets, if R2T 14 Part of the light rare earth elements (mainly Nd and / or Pr) contained in R in compound B is replaced by heavy rare earth elements (mainly Dy and / or Tb), which can increase the H cJ With the increase of heavy rare earth element substitution, H cJ Will also improve.

[0005] However, if R2T 14 The light rare earth elements in the B compound are replaced by heavy rare earth elements. cJ is improved, but the residual flux density B r (hereinafter referred to as "B r ”) will be reduced. In addition, due to the fact that heavy rare earth elements, especially Dy, have not only small reserves but also limited production areas, there are problems such as unstable supply and large price fluctuations. Therefore, in recent years, users have been demanding a method to increase H without using heavy rare earth elements as much as possible. cJ technology.

[0006] Patent Document 1 describes an RTB rare earth sintered magnet with reduced Dy content and improved coercivity. Compared with the commonly used RTB alloy, the composition of this sintered magnet is limited to a relatively small specific range of B content (boron composition ratio or boron concentration), and contains one or more metal elements selected from Al, Ga, and Cu. As a result, R2T is generated at the grain boundary. 17 phase, at the grain boundary by the R2T 17 The transition metal-rich phase (R6T 13 M) increases, thereby increasing H cJ .

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2013 / 008756 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In order to achieve both reduced content of heavy rare earth elements and high B r and high H cJ In the rare earth sintered magnets, the technology of controlling the grain boundary between the two grains to a thicker value by relatively reducing the B content has been studied.

[0012] On the other hand, the inventors found that even if the amount of rare earth elements and the B content in the raw material alloy are adjusted to the required range, the thickness of the grain boundary between the two grains cannot be fully controlled based on the manufacturing process, and there are still cases where the magnet performance deteriorates. The inventors believe that the reason is that the grain boundary phase has changed due to the oxygen content of the rare earth sintered magnet. However, the study found that even if each process in the manufacturing stage is controlled in a low-oxygen environment, it is difficult to control the fluctuation of the oxygen concentration of the final rare earth sintered magnet to below 400ppm. It was later discovered that the reason was the moisture in the raw alloy powder added to the rare earth sintered magnet.

[0013] The method for producing a rare earth system sintered magnet of the present invention can suppress the incorporation of moisture into the raw material alloy powder of the rare earth system sintered magnet during the production process.

[0014] Technical solutions to solve problems

[0015] In a certain embodiment, the method for manufacturing a rare earth sintered magnet of the present invention includes the following steps: recovering powder particles of a rare earth raw material alloy or agglomerates of the powder particles as recycled raw materials in the manufacturing process of the rare earth sintered magnet; crushing the recycled raw materials in the oil agent using a crushing device; and adjusting the ratio of the mass of water in the oil agent to the mass of the recycled raw materials in the oil agent, i.e., the water ratio in the oil agent, to less than 0.005%.

[0016] Effects of the Invention

[0017] According to the embodiment of the present invention, it is possible to suppress the incorporation of water into the raw material alloy powder of the rare earth system sintered magnet when the powdered recycled raw material obtained in the manufacturing process is pulverized in an oil agent. As a result, a rare earth system sintered magnet with modified grain boundaries can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1A Schematic diagram of the main phase and grain boundary phase of RTB sintered magnet.

[0019] Figure 1B for Figure 1A A further enlarged schematic diagram of the dotted rectangular area.

[0020] Figure 2 This is a schematic flow chart showing an outline of a method for producing a rare earth system sintered magnet according to an embodiment of the present invention.

[0021] Figure 3A This is a front view for explaining the process of cutting a powder molded body immersed in oil with a saw wire.

[0022] Figure 3B It is another front view for explaining the process of cutting the powder molded body immersed in the oil with the saw wire.

[0023] Figure 4 Another schematic flow chart showing the outline of the method for producing a rare earth system sintered magnet according to an embodiment of the present invention.

[0024] Explanation of symbols

[0025] 12: Main phase

[0026] 14: Grain boundary phase

[0027] 14a: Two grain boundary phases

[0028] 14b: triple point of grain boundary DETAILED DESCRIPTION

[0029] Hereinafter, an embodiment of the present invention will be described with respect to an RTB based sintered magnet as an example of a rare earth based sintered magnet.

[0030] It is known that in conventional RTB-based sintered magnets, when, for example, (1) the content of R (at least one of the rare earth elements, but at least one of Nd and Pr) is 27% by mass or more and 34% by mass or less of the entire RTB-based sintered magnet, (2) T is at least one selected from Fe, Co, Al, Mn and Si, and T at least contains Fe, and the content of Fe relative to the entire T is 80% by mass or more, and (3) the molar ratio of T to B ([T] / [B]) is greater than 14.0 and less than 15.0, by adding an element such as Ga, the thickness of the grain boundary between the two grains can be increased and the H can be increased. cJ .

[0031] The molar ratio of T to B ([T] / [B]) is obtained by dividing the analyzed values ​​(mass %) of the concentrations of the elements constituting T (Fe or at least one of Co, Al, Mn, and Si and Fe) by the atomic weight of each element, and then calculating the ratio (a / b) of the total molar number of these values ​​(a) and the analyzed value (mass %) of the B concentration divided by the molar number of the atomic weight of B (b).

[0032] The molar ratio of T to B ([T] / [B]) greater than 14.0 means that the content ratio of B is lower than R2T 14 In this case, in the RTB based sintered magnet, the main phase (R2T 14 Compared with the amount of T used to form compound B, the amount of B is relatively reduced.

[0033] Next, the basic structure of the RTB based sintered magnet will be described.

[0034] RTB sintered magnets have a structure in which the powder particles of the raw material alloy are bonded by sintering. 14 A main phase of the B compound and a grain boundary phase located at the grain boundary portion of the main phase.

[0035] Figure 1A Schematic diagram of the main phase and grain boundary phase of RTB sintered magnet. Figure 1B for Figure 1A A further enlarged schematic diagram of the dotted rectangular area. Figure 1A As an example, an arrow with a length of 5 μm is recorded as a reference length indicating a size. Figure 1A and Figure 1B As shown, RTB sintered magnets mainly include R2T 14 The main phase 12 of the B compound and the grain boundary phase 14 located at the grain boundary portion of the main phase 12. In addition, Figure 1B As shown, the grain boundary phase 14 includes two R2T 14The grain boundary phase 14a between two adjacent B compound particles (grains) and three or more R2T 14 The triple point 14b of the grain boundary between adjacent B compound grains.

[0036] R2T of main phase 12 14 Compound B is a ferromagnetic phase with high saturation magnetization (intensity) and anisotropic magnetic field. Therefore, in RTB based sintered magnets, by increasing the R2T 14 The presence ratio of B compounds can increase the r To improve R2T 14 The ratio of the B compound is preferably such that the R content, T content, and B content in the raw material alloy are close to R2T 14 The stoichiometric ratio of the B compound (R content: T content: B content = 2:14:1). 14 When the B content or R content of the B compound is lower than the stoichiometric ratio, Fe phase or R2T phase is usually generated in the grain boundary phase 14. 17 Equal soft magnetic phase, so that H cJ However, if the B content is less than R2T 14 The stoichiometric ratio of the B compound and the metal element M selected from Al, Ga, and Cu are formed by R2T 17 The transition metal-rich phase (such as RT-Ga phase) is generated to increase the thickness of the grain boundary between the two grains, and as a result, high H cJ .

[0037] In RTB-based sintered magnets, in order to increase the thickness of the grain boundary between two crystal grains, it is important to control not only the B content but also the oxygen content. After research, the inventors found that in order to accurately control the oxygen content in the raw material of RTB-based sintered magnets within a set range, in the manufacturing process of rare earth-based sintered magnets, when the powder particles or agglomerates of powder particles of rare earth-based raw material alloys are recovered as recycled raw materials and the recycled raw materials are crushed by a crushing device storing an oil agent, it is important to suppress oxidation caused by the moisture in the above-mentioned oil agent. In addition, in an embodiment of the present invention, the water content of the oil agent is not simply reduced by managing and controlling the water content of the oil agent according to the quality of the recycled raw materials in the oil agent of the oil agent stored in the crushing device, so that the control of powder oxidation can be achieved more effectively.

[0038] <Implementation Method>

[0039] Next, refer to Figure 2 The following is an overview of a method for producing a rare earth sintered magnet according to an embodiment of the present invention. Figure 2As shown, the method for manufacturing a rare earth sintered magnet in this embodiment includes a step of recovering powder particles or agglomerates of powder particles of a rare earth raw material alloy as a recycled raw material in the manufacturing process of a rare earth sintered magnet (S10); a step of crushing the recycled raw material in an oil agent using a crushing device (S12); and a step of adjusting the ratio of the mass of water in the oil agent to the mass of the above-mentioned recycled raw material in the oil agent, that is, the water ratio in the oil agent, to less than 0.005% (S14).

[0040] The important point of the manufacturing method according to the embodiment of the present invention is to adjust the "water ratio" in the oil solution stored in the pulverizing device to 0.005% or less. The technical effect of such execution will be described later.

[0041] Each step of the production method of this embodiment including the above-mentioned steps will be described below.

[0042] <Rare Earth Alloy Powder Formation Process>

[0043] In this embodiment, as a process (fine grinding process) of grinding the raw alloy to obtain rare earth alloy powder, it is a process of forming rare earth alloy powder by a jet mill grinding device. Preferably, before the fine grinding process, a hydrogen crushing process is performed to prepare a coarse crushed powder of the rare earth alloy. The composition of the rare earth raw alloy is as follows, including:

[0044] R: 26.5 to 33.5 mass % (R is a rare earth element and must contain at least one of Nd and Pr),

[0045] M: 0.20 to 1.50 mass % (M is at least one selected from Ga, Cu, Zn, Al and Si, and must contain Cu),

[0046] B: 0.85-0.92% by mass

[0047] T: 61.5 mass % or more, (T is Fe and Co, and 90% or more of T is Fe in terms of mass ratio),

[0048] and,

[0049] Tb: 0.30 mass% or less, and

[0050] Dy: 0.30 mass % or less.

[0051] By adjusting the B content to the above range, R6T is formed at the grain boundaries of the rare earth sintered magnet. 13 Ga and thickening the grain boundaries between the two grains, it is possible to achieve, for example, a B of 1.39T or more. r and high H above 1640kA / m cJIn order to ensure thickening of the grain boundaries between the two crystal grains, the molar ratio of T ([T] / [B]) is more preferably higher than 14.0 and lower than 15.0.

[0052] The rare earth alloy raw material having the above composition can be prepared by, for example, a thin strip continuous casting method. The rare earth alloy can include a plurality of alloy components with different compositions. By making the whole have the above composition, it is possible to achieve thickening of the above two grain boundaries and achieving high H cJ effect.

[0053] The hydrogen crushing process may include a hydrogen storage process in which hydrogen is stored in the above-mentioned rare earth alloy at a temperature below 200°C in a processing chamber; and a dehydrogenation process in which hydrogen is discharged from the processing chamber, the rare earth alloy is heated in a range of, for example, above 80°C and below 650°C, and a dehydrogenation treatment is performed to prepare a coarsely crushed powder.

[0054] The average particle size of the coarsely crushed powder is, for example, 10 μm or more and 500 μm or less. It should be noted that the average particle size (d50) in the present invention can be measured by airflow dispersion laser diffraction method (according to JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size refers to the particle size (median particle size: d50) when the cumulative particle size distribution (volume basis) calculated from the small particle size side reaches 50%.

[0055] In the fine grinding process, the coarse crushed powder can be crushed to obtain a fine powder with a median particle size d50 of, for example, 3.5 μm or less. The fine grinding process may include a step of mixing an organic grinding aid with the coarse crushed powder. As an organic grinding aid, for example, zinc stearate can be cited. The average particle size d50 of the finely crushed powder is preferably 2.0 μm or more and 3.5 μm or less.

[0056] The method for manufacturing a rare earth sintered magnet includes a step of preparing a powder molded body using the finely pulverized powder prepared by the above method, and a step of preparing a raw material for a rare earth sintered magnet by sintering the powder molded body. There are roughly two types of press molding (press molding in a magnetic field) methods for preparing powder molded bodies. One is a dry molding method in which the powder is directly pressed and molded in a dry state, and the other is a wet molding method. In the wet molding method, a slurry in which powder is dispersed in oil is used, and the powder is supplied to a mold in a slurry state for press molding.

[0057] In both wet and dry molding methods, defective molded products may occur due to, for example, the powder molded body coming into contact with something during transportation, causing partial fragmentation or cracking. In addition, a powder molded body is sometimes cut and divided into a plurality of molded body pieces. Although the molded body pieces are transformed into raw materials for rare earth sintered magnets through the sintering process, the parts of the powder molded body other than the molded body pieces are not sintered and remain as "molded body scraps" or "scraps".

[0058] Since the rare earth metal used in rare earth sintered magnets is a rare element, it is necessary to effectively reuse such defective molded products and molded body scraps.

[0059] An example of a process for producing a powder molded body from the above-mentioned powder will be described below.

[0060] <Step of Preparing Powder Molded Body>

[0061] The powder molded body can be made from powder (finely pulverized powder) by, for example, pressing in a magnetic field. From the perspective of suppressing oxidation, when pressing in a magnetic field, it is preferred to form the powder molded body by pressing in an inert gas environment or wet pressing. In particular, in wet pressing, the surface of the particles constituting the powder molded body is coated with an oil agent, which suppresses contact with oxygen and water vapor in the atmosphere. Therefore, it is possible to prevent or suppress oxidation of the particles by the atmosphere before or after the pressing process or during the pressing process.

[0062] When wet pressing is performed in a magnetic field, a slurry in which an oil agent is mixed in the finely pulverized powder is prepared, supplied to the mold cavity of the mold of the wet pressing device and pressed in a magnetic field. The oil agent is a liquid that can obtain a slurry by dispersing the alloy powder inside it. As a preferred oil agent used in the present invention, mineral oil or synthetic oil can be cited. The type of mineral oil or synthetic oil is not specific, but when the kinematic viscosity at room temperature exceeds 10 cSt, the mutual binding force of the alloy powder will increase due to the increase in viscosity, which may have an adverse effect on the orientation of the alloy powder during wet molding in a magnetic field. Therefore, the kinematic viscosity of the mineral oil or synthetic oil at room temperature is preferably less than 10 cSt. And when the fractionation temperature of the mineral oil or synthetic oil exceeds 400 ° C, it is difficult to deoil after obtaining the molded body, the amount of residual carbon in the sintered body increases, and the magnetic properties may be reduced. Therefore, the fractionation temperature of the mineral oil or synthetic oil is preferably below 400 ° C. In addition, vegetable oil can be used as an oil agent. Vegetable oil refers to oil extracted from plants, and the plant species are not limited to specific plants.

[0063] The obtained alloy powder can be mixed with an oil to obtain a slurry. The mixing ratio of the alloy powder and the oil is not particularly limited, and the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. This is because the 3At a flow rate of 1000 g / min, not only can the alloy powder be efficiently supplied to the inside of the mold cavity, but also excellent magnetic properties can be obtained. The alloy powder concentration in the slurry is preferably less than 90% by mass ratio. There is no particular restriction on the mixing method of the alloy powder and the oil agent. The alloy powder and the oil agent can be prepared separately, and the two are weighed and mixed according to a predetermined amount to make them. In addition, when the coarse crushed powder is dry-crushed to obtain the alloy powder by a jet mill, etc., a recovery container equipped with an oil agent is arranged at the alloy powder discharge port of the pulverizing device such as a jet mill, and the alloy powder obtained by crushing is directly recovered in the oil agent in the recovery container to obtain a slurry. In this case, it is preferred to set the recovery container to an environment composed of nitrogen and / or argon, and the obtained alloy powder is directly recovered from the oil agent in a state without contact with the atmosphere to form a slurry. In addition, the coarse crushed powder can also be kept in the oil agent by wet crushing using a vibration mill, a ball mill or a stirred mill, etc. to obtain a slurry composed of alloy powder and an oil agent.

[0064] The slurry thus obtained is molded using a known wet pressing device to obtain a molded body having a predetermined size and shape. Specifically, the slurry is supplied to the mold cavity of the wet pressing device and pressed in a magnetic field. The powder molded body will have a density of, for example, 4 g / cm 3 Above, 5g / cm 3 The powder compact can also be formed by a dry pressing device.

[0065] <Powder compact cutting step>

[0066] In this embodiment, the powder compact obtained in the above process can be cut by a wire saw device (cutting device), and one or more compact sheets can be prepared from each powder compact. More specifically, the powder compact of the rare earth alloy raw material is placed in the oil of the wire saw device storing the oil, and the powder compact is cut in the oil.

[0067] In the following description, the cutting of the powder molded body 10 can be performed by, for example, Figure 3A and Figure 3B The wire saw device 100 shown performs. Figure 3A and Figure 3B Each of them is a front view for explaining a process of cutting the powder molded body 10 immersed in the oil 60 by the saw wire 40 . Figure 3A It shows the state before the cutting process starts. Figure 3B Indicates the status of the cutting process in progress. Figure 3B The dashed line in the powder molded body 10 shown indicates the position of the saw wire 40 during cutting of the powder molded body 10. For reference, mutually orthogonal X-axis, Y-axis and Z-axis are shown in the figure. In this example, the XY plane points to the horizontal direction and the Z axis points to the vertical direction.

[0068] In the present embodiment, the wire saw device 100 has rollers 30a, 30b, 30c whose central axes of rotation are arranged parallel to each other and a continuous saw wire 40. The rollers 30a to 30c are all supported by a supporting device not shown in the figure and are all rotatable. The rotation axes of the rollers 30a to 30c are parallel to the Y axis. The saw wire 40 is subjected to tension and moves due to the rotation of the rollers 30a to 30c. The saw wire 40 is wound onto a spool not shown in the figure. It should be noted that the wire saw device 100 may also have other rollers for adjusting the tension, etc.

[0069] The powder molded body 10 is fixed to the fixing base 20 and is arranged inside the tank 62 storing the oil 60. The powder molded body 10 is immersed in the oil 60 as a whole. The portion of the running saw wire 40 located between the rotating rollers 30a and 30b contacts the powder molded body 10. It should be noted that the support device (not shown) has a shape that can move in the Y-axis direction without interfering with the powder molded body 10 during the process of cutting the powder molded body 10 using the saw wire 40 running between the rotating rollers 30a and 30b.

[0070] In the example shown in the figure, the saw wire 40 moves in a direction perpendicular to the traveling direction of the saw wire 40 (an arbitrary direction in the YZ plane) while traveling along the X-axis direction at a set speed. The direction perpendicular to the traveling direction of the saw wire 40 is the cutting direction, and the speed in this direction (cutting speed) is set to, for example, 100 mm / min or more. Figure 3B In the example shown, the advancing saw wire 40 is shown moving along, for example, the negative direction of the Z axis relative to the stationary powder molded body 10, but as mentioned above, the powder molded body 10 can also be lifted along the positive direction of the Z axis together with the fixed base 20, and can also have a movement component in the Y axis direction.

[0071] Such a wire saw device 100 can be used to produce one or more molded body sheets of various shapes, which may have curved surfaces, from a bulk powder molded body 10 having a rectangular parallelepiped shape. In this case, unsintered scraps are also formed from each powder molded body 10 .

[0072] In this embodiment, the scraps formed by the powder molded body 10 are crushed in an oil agent by a crushing device and reused to prepare a new powder molded body. It should be noted that the powder that can be reused is not limited to a part of the powder molded body after cutting. The powder molded body itself that fails wet pressing or dry pressing can also be reused after being crushed in an oil agent. These crushable powders or powder agglomerates can also be called "recycled raw materials."

[0073] The pulverization in the oil is not limited to the state where the molded body is completely immersed in the oil, but also includes the state where the surface of the powder particles is covered with an oil film sufficient to prevent contact with oxygen in the atmosphere. The oil is a mineral oil or a synthetic oil. The oil used for the dispersion medium of the slurry can be exactly the same as that used, or a different oil can be used.

[0074] As a pulverizing method, the scraps can be pulverized into powders including, for example, 149 mesh sieves and 500 mesh not sieved. The scraps can be simply rolled with stainless steel components to achieve pulverization, or the device described in International Publication WO2011 / 125578 or International Publication WO2013 / 047429 can be used to pulverize. The ratio of the powder sieved with 149 meshes in the pulverized powder is preferably as high as possible, for example, preferably successively more than 10 mass %, more than 25 mass %, more than 50 mass %, more than 75 mass %, more than 90 mass % and 100 mass %. In this way, the yield of the regenerated powder can be further improved. In addition, in the pulverized powder, the ratio of the powder sieved with 500 meshes is as high as possible, for example, preferably successively more than 10 mass %, more than 25 mass %, more than 50 mass %, more than 75 mass %, more than 90 mass % and 100 mass %. In this way, compared with the prior art that all 500 mesh sieves are formed in the pulverizing process, the pulverizing required time can be further shortened. More preferably, the powder after pulverization consists of powder that passes through a 149-mesh sieve and does not pass through a 500-mesh sieve. It should be noted that the state of the powder after pulverization is not limited to the above example.

[0075] In this embodiment, the ratio of the mass of water in the oil stored in the pulverizing device to the mass of the recycled raw material in the oil, that is, the water ratio in the oil is adjusted to 0.005% or less. In the embodiment of the present invention, the water ratio of the ratio of "the mass of water in the oil" to "the mass of the powder (recovered powder) in the oil" is adjusted to 0.005% or less, not simply by reducing the water content of the oil. This is because the water content in the oil can be adjusted by, for example, passing an inert gas into the oil to reduce the water content in the oil.

[0076] The inventors of the present invention have found through experiments that by adjusting the above-mentioned "water ratio" to 0.005% or less, the oxygen increment of the rare earth sintered magnet produced by, for example, a 60-minute or more oil pulverization process can be controlled to 0.040 mass% or less. The preferred value of the water ratio is 0.002% or less. It should be noted that the above-mentioned water ratio can be measured using a known oil moisture meter, such as TEKHNEPort-Oil manufactured by TEKHNE Corporation.

[0077] Next refer to Figure 4, describing other process examples of the method for manufacturing a rare earth sintered magnet of the present embodiment. The method for manufacturing a rare earth alloy of the present embodiment includes: a process (S18) of preparing a powder compact including powder obtained by crushing a recycled raw material using a crushing device, and a process (S20) of sintering the powder compact to prepare a raw material for a rare earth sintered magnet, preferably also including a process (S22) of preparing a diffusion source powder formed of an RMA alloy; and a process (S24) of diffusing the elements contained in the diffusion source powder into the interior of the raw material for a rare earth sintered magnet.

[0078] <Step (S18) of preparing a powder compact comprising crushing the recycled raw material with a crushing device>

[0079] This step can be performed in the same manner as the above-mentioned <powder molded body preparation step>. Specifically, the powder obtained by crushing the recycled raw material by the crushing device as described above can be mixed with the powder prepared by, for example, a jet mill crushing device for reuse. For example, the mixed slurry can be used to make a new powder molded body by the above-mentioned wet pressing. It should be noted that the powder obtained by crushing in oil can also be reused to obtain the raw alloy instead of being used in such a pressing step.

[0080] <Preparation Step of Rare Earth Sintered Magnet Raw Material (S20)>

[0081] Next, the powder compact is sintered to obtain a rare earth system sintered magnet (sintered body).

[0082] The sintering of the powder molded body is preferably carried out in the range of 1000°C to 1150°C. In order to prevent oxidation caused by sintering, the residual gas in the environment can be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably heat-treated. The magnetic properties can be improved by heat treatment. The heat treatment conditions such as heat treatment temperature and heat treatment time can adopt known conditions. The rare earth sintered magnet obtained in this way can be subjected to a grinding / polishing process, a surface treatment process and a magnetization process as needed to complete the final rare earth sintered magnet.

[0083] <Step of Preparing Diffusion Source Powder (S22)>

[0084] In the diffusion source RMA alloy, R is at least one rare earth element and contains at least one of Nd and Pr. M is at least one selected from Cu, Ga, Co and Fe. A is at least one selected from Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag and B.

[0085] The composition ratio of R is 65 mass % or more and 95 mass % or less of the entire RMA alloy, the composition ratio of M is 5 mass % or more and 35 mass % or less of the entire RMA alloy, and the composition ratio of A is 0 mass % or more and 3 mass % or less of the entire RMA alloy.

[0086] The diffusion source can be prepared by using a raw material alloy preparation method used in a common manufacturing method represented by Nd-Fe-B system sintered magnet, such as a mold casting method, a thin strip continuous casting method, a single roll super quenching method (melt spinning method), an atomization method, etc. In addition, the diffusion source can also be a pulverized product obtained by pulverizing the alloy obtained above by a known pulverizing device such as a pin mill. In addition, in order to improve the pulverizability of the alloy obtained by the above method, a heat treatment below 700°C can be performed in a hydrogen environment to allow the material to contain hydrogen before pulverization.

[0087] <Diffusion Step of Elements Contained in Diffusion Source Powder (S24)>

[0088] By performing heat treatment at a temperature of 700°C to 1100°C in a vacuum or inert gas environment, the elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. In the present invention, this heat treatment is referred to as the first heat treatment. When the heat treatment temperature for diffusion is lower than 700°C, the diffusion may be insufficient and high H may not be obtained. cJ On the other hand, when the temperature exceeds 1100°C, abnormal grain growth occurs in the main phase, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. This is because a higher H cJ It should be noted that the heat treatment time can be set to an appropriate value according to the composition, size, heat treatment temperature, etc. of the sintered material and the diffusion source, preferably more than 5 minutes and less than 30 hours, more preferably more than 10 minutes and less than 25 hours, and further preferably more than 30 minutes and less than 20 hours. In addition, it is preferred to prepare a diffusion source of more than 1 mass % and less than 30 mass % relative to the weight of the sintered material. When the diffusion source is less than 1 mass % relative to the weight of the sintered material, H cJ On the other hand, if it exceeds 30% by mass, B r It is possible to reduce.

[0089] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the first heat treatment can be performed by covering the surface of the sintered body material with a powder layer of the diffusion source. For example, the first heat treatment can be performed after the diffusion source is applied to the surface of the sintered body material by sputtering. For example, the diffusion source can also be applied to the surface of the sintered material by evaporating the dispersion medium after a slurry in which the diffusion source is dispersed in a dispersion medium is applied to the surface of the sintered material. It should be noted that as dispersion media, alcohols (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes and ketones can be cited as examples. In addition, the sintered body material that has been subjected to the first heat treatment can also be subjected to known mechanical processing such as cutting and machining.

[0090] The sintered material after the heat treatment for diffusion can be heat treated at a temperature of 450°C to 600°C in a vacuum or inert gas environment. In the present invention, this heat treatment is referred to as the second heat treatment. By performing the second heat treatment, a high B r and high H cJ By setting the second heat treatment temperature to 450°C or higher and 600°C or lower, R6T can be performed. 13 The second heat treatment temperature is preferably 480°C or higher and 560°C or lower. cJ It should be noted that the heat treatment time can be set to an appropriate value according to the composition, size, heat treatment temperature, etc. of the sintered body material, and is preferably 5 minutes or more and 20 hours or less, more preferably 10 minutes or more and 15 hours or less, and further preferably 30 minutes or more and 10 hours or less.

[0091] According to this embodiment, when powder or powder agglomerates recovered as recycled raw materials in the manufacturing process are crushed in an oil, oxidation of powder particles due to water in the oil can be suppressed. As a result, a rare earth sintered magnet with modified grain boundaries can be realized.

[0092] Example

[0093] The present invention will be described in more detail below through experimental examples (including embodiments and comparative examples), but the present invention is not limited thereto.

[0094] Example 1

[0095] A rare earth raw material alloy (alloy for RTB sintered magnet) shown in Table 1 Sample No. 1 was prepared. Specifically, alloys of various elements were prepared according to the composition shown in Table 1 Sample No. 1, and the alloy for RTB sintered magnet was prepared by a thin strip continuous casting method. The obtained alloy for RTB sintered magnet was coarsely crushed by hydrogen crushing to obtain a coarse crushed powder. The coarse crushed powder was put into a jet mill pulverizing device, and the coarse crushed powder was crushed to obtain a fine powder. The average particle size (d50) of the obtained fine powder is 3.0μm. The average particle size (d50) was measured in a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, range: R2, and calculation mode: HRLD.

[0096] The obtained fine powder was immersed in mineral oil to prepare a slurry. The slurry concentration was 75% by mass. The obtained slurry was molded in a magnetic field (wet molding) to obtain a powder molded body A. It should be noted that the molding device used a so-called right-angle magnetic field molding device (transverse magnetic field molding device) in which the direction of the applied magnetic field was orthogonal to the compression direction.

[0097] The obtained powder molded body A is recovered as a recycling raw material, and the above-mentioned recycling raw material is crushed in the above-mentioned oil agent using a crushing device that can store oil agent. Specifically, it is crushed into a powder containing 149 mesh sieved and 500 mesh not sieved. The crushing time is about 60 minutes. The ratio of the mass of water in the oil agent stored in the crushing device to the mass of the recycled raw material in the oil agent, that is, the water ratio of the oil agent is adjusted as shown in Table 2. The water ratio was measured using TEKHNEPort-Oil, a moisture meter for oil production produced by TEKHNE Corporation.

[0098] Then, the fine powder obtained by crushing the recycled raw material using a crushing device was immersed in mineral oil to make a slurry. The slurry concentration was 75% by mass. The obtained slurry was molded in a magnetic field (wet molding) to obtain a powder molded body B. The above-mentioned powder molded body B was sintered in a vacuum at a temperature of 1050°C (a temperature sufficient to achieve full densification by sintering) for 4 hours to obtain a sintered body. The density of the sintered body is 7.5Mg / m 3 The sintered body was heat treated by keeping it at 800°C for 2 hours and then cooling it to room temperature, and then keeping it at 500°C for 2 hours and then cooling it to room temperature, to obtain RTB based sintered magnets (No. 1 to 8).

[0099] The O (oxygen content) of the obtained sintered magnet was measured by gas melting-infrared absorption method. The results are shown in Table 2. In addition, the above-mentioned powder molded body A was made into an RTB system sintered magnet (No.A, RTB system sintered magnet without crushing) in the same way. After measuring the oxygen content of the finished product, it was found that the oxygen content was 0.095% by mass. The difference in oxygen content (Δ oxygen content) between the RTB system sintered magnet No.A and the RTB system sintered magnets No.1 to 8 is shown in Table 2.

[0100] [Table 1]

[0101]

[0102] [Table 2]

[0103]

[0104] As shown in Table 2, the oxygen content of the examples (No. 3, 6, 8) of the present invention is lower than that of the comparative examples (No. 1, 2, 4, 5, 7), and the Δ oxygen content is also controlled below 400 ppm.

[0105] As described above, the present invention relates to a method for producing a rare earth system sintered magnet as described in the following items.

[0106] [Item 1]

[0107] A method for manufacturing a rare earth sintered magnet, comprising:

[0108] In the process of manufacturing a rare earth sintered magnet, a step of recovering powder particles of a rare earth raw material alloy or agglomerates of the powder particles as a recycling raw material;

[0109] The step of crushing the recycled raw material in the oil solution using a crushing device; and

[0110] A step of adjusting the ratio of the mass of water in the oil to the mass of the recycled raw material in the oil, that is, the water ratio in the oil, to 0.005% or less.

[0111] [Item 2]

[0112] In the method for producing a rare earth sintered magnet according to item 1, the step of adjusting the water content to 0.005% or less includes the step of introducing an inert gas into the oil to reduce the amount of water in the oil.

[0113] [Item 3]

[0114] The method for producing a rare earth sintered magnet according to item 1 or 2, wherein:

[0115] The composition of the rare earth raw material alloy includes:

[0116] R: 26.5-33.5 mass % (R is a rare earth element and must contain at least one of Nd and Pr);

[0117] M: 0.20-1.50 mass % (M is at least one selected from Ga, Cu, Zn, Al and Si, and must contain Cu);

[0118] B: 0.85-0.92 mass%;

[0119] T: 61.5 mass % or more, (T is Fe and Co, and 90% or more of T is Fe in terms of mass ratio),

[0120] and,

[0121] Tb: 0.30 mass% or less, and

[0122] Dy: 0.30 mass % or less.

[0123] [Item 4]

[0124] The method for producing a rare earth sintered magnet according to any one of items 1 to 3, further comprising:

[0125] a step of preparing a powder compact comprising crushing the recycled raw material using the crushing device;

[0126] A step of sintering the powder compact to prepare a raw material for a rare earth sintered magnet;

[0127] a step of preparing a diffusion source powder formed of an RMA alloy; and

[0128] a step of heat treating the diffusion source powder while it is attached to the surface of the rare earth system sintered magnet material to diffuse the elements contained in the diffusion source powder into the interior of the rare earth system sintered magnet material;

[0129] In the above RMA alloys,

[0130] R is at least one rare earth element and includes at least one of Nd and Pr,

[0131] M is at least one selected from Cu, Ga, Co and Fe,

[0132] A is at least one selected from Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag and B,

[0133] The composition ratio of R is 65 mass % or more and 95 mass % or less of the entire RMA alloy.

[0134] The composition ratio of M is 5 mass % or more and 35 mass % or less of the entire RMA alloy.

[0135] The composition ratio of A is not less than 0 mass % and not more than 3 mass % of the entire RMA alloy.

Claims

1. A method for producing a rare earth sintered magnet, comprising: In the process of manufacturing a rare earth sintered magnet, a step of recovering powder particles of a rare earth alloy raw material or agglomerates of the powder particles as a recycling raw material; The step of crushing the recycled raw material in an oil agent using a crushing device; and A step of adjusting the ratio of the mass of water in the oil to the mass of the recycled raw material in the oil, that is, the water ratio in the oil, to 0.005% or less.

2. The method for producing a rare earth sintered magnet according to claim 1, wherein: The step of adjusting the water content to 0.005% or less includes the step of introducing an inert gas into the oil to reduce the amount of water in the oil.

3. The method for producing a rare earth sintered magnet according to claim 2, wherein: The composition of the rare earth raw material alloy comprises: R: 26.5-33.5 mass %, wherein R is a rare earth element and must contain at least one of Nd and Pr; M: 0.20-1.50 mass %, wherein M is at least one selected from Ga, Cu, Zn, Al and Si, and must contain Cu; B: 0.85-0.92 mass%; T: 61.5 mass % or more, wherein T is Fe and Co, and in terms of mass ratio, 90% or more of T is Fe, and, Tb: 0.30 mass% or less, and Dy: 0.30 mass % or less.

4. The method for producing a rare earth sintered magnet according to any one of claims 1 to 3, further comprising: a step of preparing a powder compact comprising crushing the recycled raw material into powder using the crushing device; A step of sintering the powder compact to prepare a raw material for a rare earth sintered magnet; a step of preparing a diffusion source powder formed of an RMA alloy; and a step of performing heat treatment while the diffusion source powder is attached to the surface of the rare earth system sintered magnet material to diffuse the elements contained in the diffusion source powder into the interior of the rare earth system sintered magnet material; In the RMA alloy, R is at least one rare earth element and includes at least one of Nd and Pr, M is at least one selected from Cu, Ga, Co and Fe, A is at least one selected from Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag and B, The composition ratio of R is 65 mass % or more and 95 mass % or less of the entire RMA alloy. The composition ratio of M is 5 mass % or more and 35 mass % or less of the entire RMA alloy. The composition ratio of A is not less than 0 mass % and not more than 3 mass % of the entire RMA alloy.

Citation Information

Patent Citations

  • Method for recycling slurry, method for manufacturing rare-earth based sintered magnet, and apparatus for recycling slurry

    WO2011125578A1

  • Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor

    WO2013008756A1

  • Regeneration method and regeneration apparatus for powder for rare earth sintered magnet

    WO2013047429A1